"(r) You Saying Yes to the Dress?": Rhoticity on a Bridal Reality Television Show. (June 2015) - Eberhardt, Maeve; Downs, Corinne
This paper investigates variation in rhoticity on the reality television show Say Yes to the Dress. The study examines the speech of five bridal consultants working at Kleinfeld Bridal in Manhattan. Using the brides' budgets as a proxy for social status, we ask whether variation in the consultants' use of (r) correlates with the amount of money the bride states she is willing to spend on her dress, which ranges from $1, 500 to unlimited. Mixed-effect logistic regression analysis shows significant differences across three budget categories, a finding that echoes Labov's original department store study as well as later replications. We discuss our findings within the frame of an audience design approach to style-shifting and the reality television genre and explore how such a mediated data source can be a fruitful area for sociolinguistic research.